Thank you for being concerned and sensitive - Henry, Jim, 1962- (Iowa short fiction award., 1997)
Twelve stories about things falling apart. In Mouthfeel, a marriage falls apart when the wife decides her life has no purpose, while Congressman Spoonbender is on a politician who discovers his life is without meaning.